Polímero hidroretentor na produção e crescimento em campo de mudas de três espécies florestais nativas - Angelos, Jacyelli Sgranci (2024)
The demand for reforestation is proportional to population growth and the use of areas for agricultural and industrial production. However, there are many obstacles encountered for reforestation to happen effectively. Among these obstacles is the use of water and the nutritional supply of planted forests. With the reduction of drinking water in the world, alternatives are needed to make the best use of water in the seedling production process. Given the statement that there are few works related to inputs that make better use of water, this dissertation was divided into two chapters, with the general objective of evaluating the influence of the use of water-retaining polymer on growth, leaf nutrition and morphology in seedling production. of 3 native forest species in the nursery phase and in the field. Chapter I aimed to verify the feasibility of using dry hydrogel, together with the substrate, in the production of seedlings of 3 forest species. Two treatments were evaluated, T1 (substrate without hydrogel) and T2 (substrate with hydrogel). A Randomized Block Design was adopted, with plots of 19 plants and 3 replications. Growth data in height and collar diameter were evaluated using regression analysis and other data were evaluated using mean test (ANOVA). The parameters determined were: chemical analysis of the substrate and leaves, height, stem diameter, dry biomass, leaf area, SPAD and Dickson quality index. For the species of Dalbergia nigra (Vell.) Fr. All. ex Benth, the presence of the hydrogel promoted a reduction in growth parameters. For the other species, Colubrina glandulosa (Perkins) and Samanea tubulosa (Bentham) Barneby Grimes, the hydrogel showed no disparity in statistical tests for all parameters, showing that its addition to the substrate did not provide better plant growth values. Chapter ll aimed to investigate the viability in the field of seedlings produced in a nursery using dry hydrogel on the substrate for the species of Dalbergia nigra (Vell.) Fr. All. ex Benth, Colubrina glandulosa (Perkins) and Samanea tubulosa (Bentham) Barneby Grimes. The treatments evaluated were respectively the same as those used in chapter 1, consisting of: T1 (seedlings produced without adding the hydrogel to the substrate) and T2 (seedlings produced with the addition of the hydrogel to the 13 substrate). The experiment was implemented in the experimental area of the Ifes Campus in Alegre and was carried out in a randomized block design containing 10 plants and 3 replications, where the efficiency and setting of seedlings in the field without the addition of irrigation were tested. The height and diameter of the seedlings were evaluated throughout the experiment. At the end of the study, the dry biomass of the root, stem, leaf and leaf area was measured. The data were processed and according to the results, seedlings with the presence of hydrogel showed a lower growth curve for both stem diameter and height. In general, there was no significant effect of the water-retaining polymer on obtaining biomass of the species analyzed, with the exception of the dry matter ratio of the aerial part and the root system, which showed that the hydrogel was harmful in obtaining this variable